Comparative Genomics of Candidatus Methylomirabilis Species and Description of Ca. Methylomirabilis Lanthanidiphila - Versantvoort, Wouter; Guerrero-Cruz, Simon; Speth, Daan R.; Frank, Jeroen; Gambelli, Lavinia; Cremers, Geert; van Alen, Theo; Jetten, Mike S. M.; Kartal, Boran; Op den Camp, Huub J. M.; Reimann, Joachim (Frontiers in Microbiology, 2018)
Methane is a potent greenhouse gas, which can be converted by microorganism at the expense of oxygen, nitrate, nitrite, metal-oxides or sulfate. The bacterium ‘Candidatus Methylomirabilis oxyfera’, a member of the NC10 phylum, is capable of nitrite-dependent anaerobic methane oxidation. Prolonged enrichment of ‘Ca. M. oxyfera’ with cerium added as trace element and without nitrate resulted in the shift of the dominant species. Here, we present a high quality draft genome of the new species ‘Candidatus Methylomirabilis lanthanophilum’ and use comparative genomics to analyze its metabolic potential in both nitrogen and carbon cycling. To distinguish between gene content specific for the ‘Ca. Methylomirabilis’ genus and the NC10 phylum, the genome of a distantly related NC10 phylum member, CSP1-5, an aerobic methylotroph, is included in the analysis. All genes for the conversion of nitrite to N2 identified in ‘Ca. M. oxyfera’ are conserved in ‘Ca. M. lanthanophilum’, including the two putative genes for NO dismutase. In addition both species have several heme-copper oxidases potentially involved in NO and O2 respiration. For the oxidation of methane ‘Ca. Methylomirabilis’ species encode a membrane bound methane monooxygenase. CSP1-5 can act as a methylotroph, but lacks the ability to activate methane. In contrast to ‘Ca. M. oxyfera’, which harbors three methanol dehydrogenases, both CSP1-5 and ‘Ca. M. lanthanophilum’ only encode a lanthanide-dependent XoxF-type methanol dehydrogenase, once more underlining the importance of rare earth elements for methylotrophic bacteria. The pathways for the subsequent oxidation of formaldehyde to carbon dioxide and for the Calvin-Benson-Bassham cycle are conserved in all species. Furthermore, CSP1-5 can only interconvert nitrate and nitrite, but lacks subsequent nitrite or NO reductases. Thus, it appears that although the conversion of methanol to carbon dioxide is present in several NC10 phylum bacteria, the coupling of nitrite reduction to the oxidation of methane is a trait so far unique to the genus ‘Ca. Methylomirabilis’.